Аналіз можливостей використання сам/сad-систем delcam для виробництва пресованих деталей - Гавриленко, Євген Андрійович; Мацулевич, Олександр Євгенович; Антонова, Галина Володимирівна; Супрун, Максим Володимирович; Havrylenko, Yevhen; Matsulevych, Oleksandr; Antonova, Halyna; Suprun, Maksym (Запоріжжя : Видавничій дім "Гельветика", 2025)
UA: Комп’ютерне моделювання виробів із полімерних матеріалів і проєктування прес-форми для їх виготовлення ґрунтується на застосуванні сучасних систем автоматизованого проєктування та забезпечує високу продуктивність і якість виготовлення виробів із полімерних матеріалів шляхом застосування технології лиття під тиском. У роботі розглянуто можливості вдосконалення проєктування ливарного оснащення за допомогою використання CAD/CAM-систем фірми Delcam і верстатів із ЧПУ. Це дає можливість підвищити якість продукції, що досягається шляхом зменшення похибок базування через багаторазові перестановки. У разі використання цієї технології зменшується трудомісткість деталі, а отже, її собівартість. Метою цієї роботи було сконструювати прес-форму для лиття під тиском і, крім того, розробити керуючу програму в середовищі PowerMILL для фрезерної обробки її компонентів. /// EN: The modern market actively uses plastic products due to their lightness, strength, and cost-effectiveness. The most common method of manufacturing them is injection molding (which accounts for more than a third of the total volume). This process is used for serial and mass production and is inextricably linked to the development of molds. To ensure competitiveness and manufacturability, especially when working with complex products, it is necessary to use CNC machines and automated design systems. Difficulties arise when ensuring the operational requirements for the product and the technological requirements for the design of casting equipment. To solve this problem, in our opinion, it is necessary to involve specialists who simultaneously possess the skills of automated design of casting equipment and the skills of creating design projects. This will make it possible to significantly reduce the time required for design work. Computer modeling of polymer products and designing molds for their manufacture is based on the use of modern computer-aided design systems and ensures high productivity and quality of polymer products through the use of injection molding technology. This work considers the possibilities of improving the design of molding equipment using Delcam CAD/CAM systems and CNC machines. In the project, processing was carried out on a three-axis CNC machine. This allows for improved product quality, achieved by reducing positioning errors through multiple repositioning. The use of this technology reduces the labor intensity of the part and, accordingly, its cost. The aim of this work was to design a mold for die casting and, in addition, to develop a control program in the PowerMILL environment for milling its components.
Analysis of the possibilities of using delcam sam/cad systems for the productio of pressed parts
Keywords: ливарне оснащення; прес-форма; кронштейн; матриця; чорнове фрезерування; чистове фрезерування; візуалізація; casting equipment; mold; bracket; die; rough milling; finish milling; visualization